Peningkatan Minat Generasi Petani Muda Melalui Program Digitalisasi Guna Peningkatan Kewirausahaan Pertanian dan Implikasinya Terhadap Ketahanan Wilayah di Bogor, Jawa Barat - Yunandar, Detia Tri; Nuryanti, Nuryanti; Parasdya, Sekar Diva (Jurnal Ketahanan Nasional, 2024)
ABSTRACTCurrently, the agricultural sector in Indonesia is faced with the problem of poor regeneration of agricultural human resources. Therefore, it is necessary to have an effective strategy in an effort to overcome these problems, namely by developing entrepreneurship in the agricultural sector accompanied by efforts to build the interest and behavior of the younger generation, especially the educated younger generation, to become agricultural entrepreneurs. This study discusses the role of digitalization programs in increasing young people’s interest in agricultural entrepreneurship and its implications for regional resilience in Bogor, West Java.This research uses a qualitative approach with a case study method to deeply understand how digital resilience can influence the interest and engagement of the younger generation in agricultural entrepreneurship. This case study focuses on IPB Bogor students and alumni who participated in the Growing Young Agricultural Entrepreneurs (PWMP) activities in 2016 and 2017. Data were collected through in-depth interviews, observation, and document analysis. Then the data was analyzed using an interactive analysis model by Miles & Huberman (2014) to understand and interpret the data through an iterative process.The results showed that digital resilience plays an important role in increasing young people’s interest in agricultural entrepreneurship. Access to information in influencing the formation of the educated young generation’s attitude towards agricultural entrepreneurship, through direct self-experience is reflected by access to information through family, peer-group, school, mass media, and the internet. The digitalization program in agriculture offers a solution to increase the interest of the younger generation in agriculture, develop agricultural entrepreneurship, and strengthen regional resilience in Bogor, West Java. Through the adoption of technology, the agricultural sector can become more modern, efficient, and sustainable, creating new opportunities for the younger generation and supporting sustainable regional development.Keywords: access to information, educated youth, enterpreneurship in the